2014
DOI: 10.1175/jpo-d-13-096.1
|View full text |Cite
|
Sign up to set email alerts
|

Bidecadal Thermal Changes in the Abyssal Ocean

Abstract: A dynamically consistent state estimate is used for the period 1992-2011 to describe the changes in oceanic temperatures and heat content, with an emphasis on determining the noise background in the abyssal (below 2000 m) depths. Interpretation requires close attention to the long memory of the deep ocean, implying that meteorological forcing of decades to thousands of years ago should still be producing trendlike changes in abyssal heat content. Much of the deep-ocean volume remained unobserved. At the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 37 publications
(40 reference statements)
4
48
0
Order By: Relevance
“…Geothermal heating is not the source of abyssal warming in recent decades, with dominant terms being vertical mixing of warmer waters and advection via upwelling (e.g., Purkey and Johnson 2012). However, both mixing and geothermal heating vary spatially, and there are likely regions where the latter (despite acting on centennial time scales) is significant in the global heat budget (Purkey and Johnson 2012;de Lavergne et al 2016;Wunsch and Heimbach 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geothermal heating is not the source of abyssal warming in recent decades, with dominant terms being vertical mixing of warmer waters and advection via upwelling (e.g., Purkey and Johnson 2012). However, both mixing and geothermal heating vary spatially, and there are likely regions where the latter (despite acting on centennial time scales) is significant in the global heat budget (Purkey and Johnson 2012;de Lavergne et al 2016;Wunsch and Heimbach 2014).…”
Section: Discussionmentioning
confidence: 99%
“…On a regional scale, geothermal heating can change ocean bottom temperatures by an order of magnitude more than error estimates associated with decadal abyssal temperature trends (e.g., Emile-Geay and Madec 2009;Purkey and Johnson 2010;Kouketsu et al 2011;Wunsch and Heimbach 2014) and increase thermosteric sea level by 0.1-1 mm yr 21 (Piecuch et al 2015). Yet geothermal heating is represented inconsistently by ocean and fully coupled models.…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al [54] extended these series back to 1960 and demonstrated an increasing ocean heat uptake, the impact of volcanic eruptions, and that the spike in ocean heat uptake and subsequent decrease in the rate of ocean warming after 2000 in some studies was probably an artifact of errors in XBT bias corrections and/or incomplete ocean coverage. Wunsch and Heimbach [55] used a sophisticated data assimilation technique to infer a deep ocean cooling, in direct contrast to the direct observations of Purkey and Johnson [56]. The reason for this difference in the Wunsch and Heimbach results is unclear but could relate to the omission of the geothermal heat flux from the ocean seafloor (approximately equivalent to the difference between their results to the direct observations) or the dominance of upper ocean observations over the sparse deep observations in their analysis.…”
Section: Sea Level Contributions Steric Sea Level Changementioning
confidence: 98%
“…As a specific example of the sampling problems, consider Figure 4a, which is an estimate of the heat content, H (λ, φ), of the oceanic water column as a 20-year average (Wunsch & Heimbach 2014); λ and φ are the longitude and latitude, respectively. For present purposes, this field is taken as the truth, as it is known to computer-word accuracy on a complete global grid, permitting the near-perfect calculation of mean temperatures,…”
Section: Inhomogeneities: Signal and Samplingmentioning
confidence: 99%